2018
DOI: 10.1080/21691401.2018.1492421
|View full text |Cite
|
Sign up to set email alerts
|

Islet-like clusters derived from skeletal muscle-derived stem/progenitor cells for autologous transplantation to control type 1 diabetes in mice

Abstract: A population of muscle-derived stem/progenitor cells (MDSPCs) contained in skeletal muscle is responsible for muscle regeneration. MDSPCs from mouse muscle have been shown to be capable of differentiating into pancreatic islet-like cells. However, the potency of MDSPCs to differentiate into functional islet-like cluster remains to be confirmed. The therapeutic potential of autologous MDSPCs transplantation on type 1 diabetes still remains unclear. Here, we investigated a four-stage method to induce the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Interestingly, progenitor cells from outside of the pancreas, such as murine skeletal muscle-derived progenitor cells, have been differentiated into insulin-producing clusters by a differentiation protocol comprising four steps of culture. These progenitor cells transformed into mature β-cells during development and significantly reduced hyperglycemia and improved survival after transplantation into STZ-induced diabetic mice ( 167 ). Moreover, Yi Arial Zeng’s team identified a new population of protein C receptor-positive (Procr+) endocrine progenitor cells by single-cell RNA sequencing and that did not express known endocrine or exocrine differentiation markers of the adult mouse pancreas ( 168 ).…”
Section: Pancreatic Progenitor Cell As Another Resource Of β-Cellsmentioning
confidence: 99%
“…Interestingly, progenitor cells from outside of the pancreas, such as murine skeletal muscle-derived progenitor cells, have been differentiated into insulin-producing clusters by a differentiation protocol comprising four steps of culture. These progenitor cells transformed into mature β-cells during development and significantly reduced hyperglycemia and improved survival after transplantation into STZ-induced diabetic mice ( 167 ). Moreover, Yi Arial Zeng’s team identified a new population of protein C receptor-positive (Procr+) endocrine progenitor cells by single-cell RNA sequencing and that did not express known endocrine or exocrine differentiation markers of the adult mouse pancreas ( 168 ).…”
Section: Pancreatic Progenitor Cell As Another Resource Of β-Cellsmentioning
confidence: 99%
“…These issues led to interest in the use of Muscle-Derived Stem/Progenitor Cells (MDSPCs), which exist in skeletal muscle and have the capacity for long-term proliferation, are resistant to oxidative and inflammatory stress, and show multilineage differentiation potential [147]. To investigate the therapeutic potential of autologous MDSPCs transplantation for T1D, Lan et al applied a four-stage MDSPC differentiation protocol to generate IPCs in vitro and injected them into diabetic mice: these β-cell-like-cells effectively improved hyperglycemia and glucose intolerance and increased the survival rate in diabetic mice without the use of immunosuppressants [148].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Mitutsova et al indicated that MDSCs can differentiate into IPCs in pancreatic islets [6]. Lan et al [7] also confirmed that muscle-derived stem/progenitor cells are capable of differentiating into insulin-producing clusters. However, the underlying mechanisms of MDSCs differentiation into IPCs have not been fully characterized.…”
Section: Introductionmentioning
confidence: 96%